(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the initial outcomes of treating great and small saphenous varicose veins using the VenaSeal cyanoacrylate closure system at the 108 Military central hospital. Subjects and methods: A descriptive case series was conducted on fourteen patients (fourteen veins), including twelve great saphenous veins and two small saphenous veins, diagnosed with superficial venous insufficiency and treated with the VenaSeal system. All procedures were performed under ultrasound guidance with local anesthesia. Patients were followed clinically and by Doppler ultrasound immediately and at 1, 6, and 12 months after intervention. Results: The technical success rate was 100%, with all veins completely occluded immediately after the procedure. Two patients (14.3%) developed mild local inflammatory reactions that resolved spontaneously within 7 days, and no major complications or deep vein thrombosis were recorded. At 6 months, all patients reported significant symptom improvement, and at 12 months, one patient (7.1%) had partial distal recanalization without clinical significance. Conclusion: The VenaSeal cyanoacrylate closure system is an effective and safe method for treating great and small saphenous varicose veins.